Computerised packages and internal controls - Morgan, Huw (Henry Stewart Talks, 2019)
Computing, Accounting records, Manual accounting, Manual errors and corrections, Computerised accounting systems, Advantages and disadvantages, Security risks, Internal controls, Flowcharts